PEMANFAATAN PEMBELAJARAN BERBASIS GAME SEBAGAI INOVASI DALAM MENGATASI RENDAHNYA MOTIVASI BELAJAR - Delia Sri Agustiani; Abdul Hakim; Rahma Novianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low motivation to learn is one of the main problems in the world of education, which affects the quality of learning. This research aims to examine the use of game-based learning as an innovation to increase student learning motivation. The research method used is descriptive qualitative with literature studies from various relevant sources. The research results show that game-based learning is able to create an interactive, fun and challenging learning atmosphere, so that it can increase students' motivation, involvement and understanding of the subject matter. With proper implementation, game-based learning can be an effective strategy in responding to the challenges of 21st century education.